Time to bury dedicated hardware-based security solutions. Issue 8 (August 2017) - German, Paul
Abstract : Virtualisation and software-defined networking (SDN) have transformed the IT infrastructure landscape over the past decade. As organisations look to minimise their hardware footprint, improve network flexibility and decouple applications from the infrastructure to gain agility and flexibility, the era of dedicated hardware-based solutions is over.